1993
DOI: 10.1056/nejm199309233291303
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Dystrophin Expression after Activation of Myogenesis in Amniocytes, Chorionic-Villus Cells, and Fibroblasts -- A New Method for Diagnosing Duchenne's Muscular Dystrophy

Abstract: Immunocytochemical analysis of dystrophin in genetically altered non-muscle cells is feasible and may be applicable to the prenatal and postnatal diagnosis of Duchenne's muscular dystrophy when conventional DNA analysis is not informative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…Therefore, to analyze the chromatin structure in the region of the hypersensitive site in skeletal muscle cells, DM fibroblasts were infected with a retrovirus expressing the myogenic determination gene MyoD and the selectable marker neomycin phosphotransferase. Previous work has shown that the expression of MyoD can convert fibroblasts to skeletal muscle cells (13,15), and this approach was used because primary muscle cultures from affected individuals were not available. After selection in G418 the MyoD-expressing cells demonstrated conversion to a skeletal muscle phenotype (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, to analyze the chromatin structure in the region of the hypersensitive site in skeletal muscle cells, DM fibroblasts were infected with a retrovirus expressing the myogenic determination gene MyoD and the selectable marker neomycin phosphotransferase. Previous work has shown that the expression of MyoD can convert fibroblasts to skeletal muscle cells (13,15), and this approach was used because primary muscle cultures from affected individuals were not available. After selection in G418 the MyoD-expressing cells demonstrated conversion to a skeletal muscle phenotype (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Since myoblasts from patient P1 were not available, fibroblasts from controls and patients P1 and P2 were converted into myoblasts by retroviral transfection of the muscle differentiation gene, MyoD, as described earlier [15]. These myoblasts were maintained in culture in the same growth medium as described above.…”
Section: Cell Culturementioning
confidence: 99%
“…MyoD, rather than a neuronal bHLH protein, was used for this analysis since the target genes for MyoD have been identified. In contrast to many nontransformed cell types, where MyoD expression is sufficient to activate skeletal myogenesis (12,50), forced expression of MyoD failed to convert a majority of tested neural tumor lines to muscle. In all cases, myogenesis was restored in heterokaryons between the tumor cells and fibroblasts, indicating that the inactivity of MyoD in the tumor cells reflected the deficiency of a factor necessary for myogenesis and allowing us to establish complementation groups among different tumors on the basis of the ability to execute a myogenic differentiation program.…”
mentioning
confidence: 63%
“…Since previous work has demonstrated that MyoD can convert many primary cells and cell lines to muscle (12,50), the inactivity of MyoD in the tumor cell lines is unusual and indicates that during tumor progression there may be a selection for alterations that prevent bHLH activity. Alternatively, the tumors may have arisen from a lineage position where the activity of MyoD, and perhaps other bHLH proteins, is precluded.…”
Section: Discussionmentioning
confidence: 99%